Experiencing In-Vivo Dosimetry Verification in Malaysia: A Patient-Specific EPID-Based Approach - Md Radzi, Yasmin; Mohsin, Ghassan Haleem; Noor Rizan, Noor Naslinda; Abdul Rahman, Azhar (Emerging Advances in Integrated Technology, 2024)
Real-time dosimetry is crucial for patient-specific quality assurance in radiotherapy facilities across Europe, and the same demand extends to advanced countries like Malaysia. Our study aimed to assess the need for in vitro diagnostic (IVD) testing in Malaysia, exploring the use of Electronic Portal Imaging Device (EPID)-based dose verification to simplify complex methods. In this research, we assessed the accuracy of in-vivo dose reconstruction using EPIgrayTM (DOSIsoft, Cachan, France) for 20 cohorts of patients who underwent breast and prostate Intensity-Modulated Radiation Therapy (IMRT) and Volumetric Modulated Arc Therapy (VMAT), and compared the results with the dose calculated by the Treatment Planning System (TPS). Initially, we set a default tolerance level of 7-10% for dose acceptance. Our study found that the majority of patients in the cohort met the 10% tolerance level when validated with EPIgrayTM in vivo dosimetry. Specifically, 12 out of 15 patients who underwent VMAT treatment were within this tolerance range. Additionally, for IMRT treatment, 4 out of 6 patients achieved the 10% tolerance level. These initial findings demonstrate the potential of EPIgrayTM as a valuable tool for verifying in vivo dosimetry for advanced treatment techniques. For VMAT plans, more than 85% of the points were in agreement with the 10% tolerance level for 11 out of 15 patients. For IMRT plans, more than 90% of the points met the set tolerance level for 4 out of 15 patients. By understanding the agreement and variability of EPID-based IVD, we can further refine the utilization of EPID-based IVD as a relevant tool in ensuring accurate and reliable dose delivery during radiotherapy treatments.